Position of art in Adorno’s thought: Art as a memory of the possible - Silva Rodríguez, Manuel Enrique (Estudios de Filosofía, 2004)
This paper intends to highlight a chronological path through same of the most important works of Theodor Adorno. Thus it is shown how in his philosophy, from the very beginning until his last great work, there was a coherent development which constituted itself in a critical model of enlightened reason, inasmuch as it can accept and represent the exciuded, and thus limited, by instrumental rationality.